When does a strategy intervention overcome a failure of inhibition? Evidence from two left frontal brain tumour cases. (June 2016) - Robinson, Gail A.; Walker, David G.; Biggs, Vivien; Shallice, Tim
Abstract: Introduction: Initiation and inhibition of responses are crucial for appropriate behaviour across different settings. Initiation and inhibition difficulties are well documented following frontal damage, although task differences have limited our understanding. The Hayling Sentence Completion Test was designed to assess verbal initiation and inhibition within the same task. This study investigates the ability of two patients with left frontal tumours (KI: high grade glioma; PM: meningioma) to use a strategy to overcome profound suppression failures on the Hayling Test. Method: KI and PM completed the Hayling Test and two experimental tasks. The Selection Investigation assessed verbal initiation on a sentence completion task that varied selection demands (high/low). The Suppression and Strategy Investigation assessed ability to implement four strategies aimed to override a suppression failure and facilitate production of an unconnected word. Results: On the Hayling Test, KI and PM initiated responses to complete high constraint sentences, in contrast to impaired suppression. KI benefitted minimally from strategies to overcome suppression failure although one strategy (object naming) was partially successful. KI's errors revealed fast suppression errors, in contrast to slow no responses, and selection ability was also impaired for verbal initiation. PM, however, implemented each strategy 100% to overcome a suppression failure and had no difficulty completing sentences meaningfully, regardless of selection demands. Conclusion: This first investigation of strategy implementation to overcome profound suppression impairments provides insights into verbal initiation, inhibition, selection and strategy mechanisms, which has implications for neurorehabilitation. Specifically, both patients had profound inhibition deficits but KI also presented with a selection deficit and was unable to implement a strategy. By contrast, PM's selection ability was intact but she was unable to generate, rather than implement, a strategy. We suggest that KI has both fast, uncontrolled semantic output and response inhibition difficulty, whereas PM's difficulty is underpinned by motivational factors.